Alkali doping strategies for flexible and light-weight Cu2ZnSnSe4 solar cells. Issue 5 (15th January 2016) - López-Marino, Simón; Sánchez, Yudania; Espíndola-Rodríguez, Moisés; Alcobé, Xavier; Xie, Haibing; Neuschitzer, Markus; Becerril, Ignacio; Giraldo, Sergio; Dimitrievska, Mirjana; Placidi, Marcel; Fourdrinier, Lionel; Izquierdo-Roca, Victor; et al.
Abstract : Different alkali doping methods to introduce Na and/or K in flexible and light-weight Cu2 ZnSnSe4 solar cells were compared. A maximum efficiency of 6.1% was achieved. Abstract : In this work we report on the effect of alkali doping via Na and/or K introduction into flexible and light-weight Cu2 ZnSnSe4 (CZTSe) solar cells obtained using a sequential process based on the sputtering of metallic stacks and further reactive annealing. Different thicknesses of Cr diffusion barriers and 50 μm thick ferritic steel substrates were used. We compare different doping methods: Na-doped Mo targets (MoNa), SLG underneath the flexible substrates, NaF and KF pre-absorber synthesis evaporation (PAS) and post-deposition evaporation (PDT). Additionally, we report on the importance of the Cr barrier and back contact modification to improve solar cell performance. A remarkable enhancement in the absorber grain size and surface morphology occurred especially when using Na via MoNa and PAS. Nevertheless, preliminary experiments led to better results for MoNa doping due to a higher Na content confirmed by TOF-SIMS. K doping via PAS also showed promising results. An increase in the efficiency of solar cells from 2.2% to 4.3% was possible when using a MoNa layer sandwiched between regular Mo layers. The improvement is mainly related to a higher V OC and FF. After performing a detailed Cr and back contact optimization, a record value of 6.1% for flexible CZTSe solar cells was recently obtained using MoNa and a new surface Ge doping.